IMPROVEMENT OF ORGANIZATIONAL CULTURE, SERVICE QUALITY AND USE OF INFORMATION TECHNOLOGY AND ITS IMPLICATIONS ON ACADEMIC PERFORMANCE IN STUDENTS OF ACCOUNTING STUDY PROGRAMS - Hiras Pasaribu; Indah Kartika Sandhi; Gita Astyka Rahmanda; Siti Rokhimah (Buletin Ekonomi: Manajemen, Ekonomi Pembangunan, Akuntansi, 2020)
This study aims to determine the effect of organizational culture which has a proxy for achievement culture, academic service quality and the use of information technology on student academic performance. The data source is derived from a questionnaire given to students of the Yogyakarta Veterans National Development Study Accounting Program. The questionnaire uses a Likert scale with a population of 1020 students. The research method uses a survey to students. The sample is done using simple random sampling. The minimum sample was taken 10% of the population, which is 102 increased to 200 students who are taking semester five to semester eight. Because students who are respondents, so far have experienced receiving academic services. The data analysis tool uses multiple regression. Primary data collected are first tested for validity, reliability, and normality and then analyzed by multiple regression. The results of this regression to determine the effect of independent variables with the dependent variable. The expected output can be an additional reference to improve the culture of achievement, service quality and implications for student academic performance. The results found that the use of information technology has a positive effect on student academic performance, while the organizational culture which is proxy from the culture of achievement, and the quality of academic services do not influence student academic performance.Penelitian ini bertujuan untuk mengetahui pengaruh budaya organisasi yang diproksikan dengan budaya berprestasi, kualitas pelayanan akademik dan penggunaan teknologi informasi terhadap prestasi akademik mahasiswa. Sumber data berasal dari angket yang diberikan kepada mahasiswa Program Studi Akuntansi Pembangunan Nasional Veteran Yogyakarta. Angket menggunakan skala likert dengan populasi 1020 siswa. Metode penelitian menggunakan survei kepada siswa. Pengambilan sampel dilakukan dengan menggunakan simple random sampling. Sampel minimal diambil 10% dari populasi yaitu 102 meningkat menjadi 200 mahasiswa yang menempuh semester lima hingga semester delapan. Pasalnya, mahasiswa yang menjadi responden, selama ini sudah berpengalaman menerima layanan akademik. Alat analisis data menggunakan regresi berganda. Data primer yang dikumpulkan terlebih dahulu diuji validitas, reliabilitas, dan normalitasnya kemudian dianalisis dengan regresi berganda. Hasil regresi ini untuk mengetahui pengaruh variabel independen dengan variabel dependen. Output yang diharapkan dapat menjadi acuan tambahan untuk meningkatkan budaya berprestasi, kualitas pelayanan dan implikasinya terhadap prestasi akademik mahasiswa. Hasil penelitian menemukan bahwa penggunaan teknologi informasi berpengaruh positif terhadap kinerja akademik mahasiswa, sedangkan budaya organisasi yang diproksikan dari budaya berprestasi, dan kualitas layanan akademik tidak berpengaruh terhadap kinerja akademik mahasiswa.